Design of Concrete Filled Tubular Beam-columns with High Strength Steel and Concrete. (November 2016) - Liew, J.Y. Richard; Xiong, Mingxiang; Xiong, Dexin
Abstract: Concrete filled steel tubular column comprising a hollow steel tube infilled with concrete has been used widely in high rise buildings. Although modern design codes provide guides on concrete filled steel tubular members, they do not cover their applications involving high strength concrete and high tensile steel. Set against this background, new tests have been conducted to supplement the dearth of research on concrete filled steel tubular members with ultra-high strength concrete (fck up to 190 N/mm 2 ) and high tensile steel (fy up to 780 N/mm 2 ). In this paper, a design guide has been proposed for concrete filled steel tubular members based on an extension of Eurocode 4 method for concrete compressive strength up to 190 N/mm 2 and high tensile steel with yield strength up to 550 N/mm 2 . More than 2030 test data collected from the literature on concrete filled steel tubes with normal and high strength materials have been analysed to formulate this design guide. This paper provides insights to this design guide sharing some of the expertise and knowledge involving the applications of high strength concrete filled tubular members in high rise buildings.